1992
DOI: 10.1029/91ja02707
|View full text |Cite
|
Sign up to set email alerts
|

Observations of a new class of upstream waves with periods near 3 seconds

Abstract: We have found a new class of ULF waves with periods near 3 s in the Earth's upstream region by examining the high time resolution magnetic field data from the ISEE spacecraft. These waves are observed in the part of the upstream region which is magnetically connected to the bow shock, but only when the solar wind plasma beta is high (greater than 1). The waves are always right‐handed, nearly circularly polarized in the spacecraft frame. The directions of the wave vectors are in the general direction of the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Wave bursts at ∼3 s periods are also detected under certain conditions (Le et al 1992). The longperiod pulsations are generated by backstreaming ions in the foreshock, andtheir wave phase velocities are directed upstream in the plasma frame, but they are swept back toward the shock with the solar wind flow (e.g., Eastwood et al 2005).…”
Section: Observationsmentioning
confidence: 99%
“…Wave bursts at ∼3 s periods are also detected under certain conditions (Le et al 1992). The longperiod pulsations are generated by backstreaming ions in the foreshock, andtheir wave phase velocities are directed upstream in the plasma frame, but they are swept back toward the shock with the solar wind flow (e.g., Eastwood et al 2005).…”
Section: Observationsmentioning
confidence: 99%
“…It includes gyrating ions upstream of the quasi-perpendicular shock (Paschmann et al 1982b), an electron foreshock extending far upstream of the bow shock , an ion foreshock (Asbridge et al 1968) consisting of reflected and diffuse ions (Gosling et al 1978) that precondition the solar wind (Paschmann et al 1979), Short Large Amplitude Magnetic Structures (SLAMS, Schwartz et al 1992), Hot Flow Anomalies (HFAs, Schwartz 1995), ion density holes (Parks et al 2006), 30 s period wave modulations of the upstream IMF (Greenstadt et al 1968;Fairfield 1969), 3 s waves (Le et al 1992), and a variety of higher frequency waves (whistler and Langmuir waves, see Gurnett et al 1979) and wave structures (electron solitary waves, Bale et al 1998). During the first 9 months of operations, all of these phenomena have been observed except for high frequency wave phenomena which THEMIS does not measure.…”
Section: Bow Shockmentioning
confidence: 99%
“…The existence of a new category of waves, called '3s waves' (Le et al, 1992), has also been reported. These waves are circularly polarised, right handed and have periods of 2 -5 s in the spacecraft frame.…”
mentioning
confidence: 97%